Examining the Landscape of Cognitive Fatigue Detection: A Comprehensive Survey - Enamul Karim; Hamza Reza Pavel; Sama Nikanfar; Aref Hebri; Ayon Roy; Harish Ram Nambiappan; Ashish Jaiswal; Glenn R. Wylie; Fillia Makedon (Technologies, 2024)
Cognitive fatigue, a state of reduced mental capacity arising from prolonged cognitive activity, poses significant challenges in various domains, from road safety to workplace productivity. Accurately detecting and mitigating cognitive fatigue is crucial for ensuring optimal performance and minimizing potential risks. This paper presents a comprehensive survey of the current landscape in cognitive fatigue detection. We systematically review various approaches, encompassing physiological, behavioral, and performance-based measures, for robust and objective fatigue detection. The paper further analyzes different challenges, including the lack of standardized ground truth and the need for context-aware fatigue assessment. This survey aims to serve as a valuable resource for researchers and practitioners seeking to understand and address the multifaceted challenge of cognitive fatigue detection.